Equal sacrifice and fair burden sharing in a public goods economy - Wolfgang Buchholz; Wolfgang Peters (Center for Economic Studies and ifo Institute (CESifo), 2007)
Applying a willingness to pay approach known from contingent valuation in environmental economics, we develop an ordinally based measure for the size of individual sacrifice that is connected with an agent's contribution to a public good. We construct a selection mechanism that picks the unique efficient solution among all allocations that have an equal sacrifice as defined in this way. We show that the solution thus obtained correspond to Moulin's egalitarian equivalent allocation, conforms to both the ability to pay and the benefit principles, and has much in common with the Lindahl equilibrium.
Keywords: H41; 330; Öffentliches Gut; Gerechtigkeit; Willingness to pay; Äquivalenzprinzip; Theorie